EFFECTIVENESS OF WORDWALL MEDIA IN INCREASING STUDENT ENGAGEMENT IN PAI LEARNING - Lunggihni Sifa; Nurjanah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This study aims to assess the effectiveness of Wordwall in enhancing student engagement to learning outcomes in Islamic Religious Education (PAI) at SMAN 74 Jakarta. Combining quantitative and qualitative data using a mixed approaches approach, the research compares Wordwall with Google Form using pretest and posttest on two student groups (experimental and control), each consisting of 30 students, along with interviews conducted with 6 students from the experimental group. The findings reveal that Wordwall significantly boosted student engagement and learning outcomes compared to Google Form. Data analysis with SPSS showed that the mean scorewas 91.67 with a standard deviation of 7.915 for the experimental group, whereas the control group had a mean score of 88.33 with a standard deviation of 6.477. Interviews further supported these findings, indicating that Wordwall's interactive nature facilitated better understanding of the material. The study confirms Wordwall's potential as an effective digital learning tool